2022
DOI: 10.3390/jcm11236998
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of Scoliosis Measurements Obtained with Surface Topography Techniques: A Systematic Review

Abstract: Background. Surface topography (ST) is one of the methods in scoliosis assessment. This study aimed to systematically review the reliability and validity of the ST measurements for assessing scoliosis. Methods. A literature search of four databases was performed and is reported following PRISMA guidelines. The methodological quality was evaluated using Brink and Louw appraisal tool and data extraction was performed. The results were analyzed and synthesized qualitatively using the level of evidence method. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
(241 reference statements)
1
7
0
Order By: Relevance
“…These values are near the 5 • margin of error of Cobb angle measurement performed on radiography [36][37][38], with almost 50% of curves with more than 5 • of difference between rasterstereography and 2D radiography. These results confirmed what the existing literature reported in a recent systematic review [31], with a good to strong correlation (r > 0.60) between rasterstereography and 2D radiography. The mean difference values are also in line with the reported mean difference in the existing literature, ranging from 5.4 • to 8.8 • [27,35].…”
Section: • Primary Objectivesupporting
confidence: 91%
See 2 more Smart Citations
“…These values are near the 5 • margin of error of Cobb angle measurement performed on radiography [36][37][38], with almost 50% of curves with more than 5 • of difference between rasterstereography and 2D radiography. These results confirmed what the existing literature reported in a recent systematic review [31], with a good to strong correlation (r > 0.60) between rasterstereography and 2D radiography. The mean difference values are also in line with the reported mean difference in the existing literature, ranging from 5.4 • to 8.8 • [27,35].…”
Section: • Primary Objectivesupporting
confidence: 91%
“…Among several commercial systems, the Formetric-4D system (Diers International GmbH, Schlangenbad, Germany) has been validated against 2D radiography by a collaborative study between the Diers company and German universities [23]. This system is largely used in research to measure and control spine deformities in AIS patients [26][27][28][29][30][31]. Most of the previous studies evaluating the validity of this system [31] concluded a good to strong correlation (r > 0.60) compared with 2D radiographs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This allows various kinematic patterns to be assessed in three dimensions 17 . It can also be considered a valuable screening tool as it is non-invasive, not harmful, so the examinations can be repeated numerous times 15 , 17 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…It is important to mention that the use of ST technology does not expose the patient to harmful radiation, unlike X-Ray 15,17,18 . In various spine diseases -repeated exposure to X-Ray may be harmful for patients 15,[17][18][19][20] .…”
mentioning
confidence: 99%